The enemies of the homeland. The representation of the other during the Spanish Civil War in the textbooks of Italian Fascism (1936-1943) - Sanz Simón, Carlos (Historia y Memoria de la Educación, 2020)
The Spanish Civil War (1936-1939) was a battlefield that, although it developed nationally, had a scope and participation that crossed the borders of Spain. The rebel side enjoyed the help of two foreign powers in challenging the Second Republic: Nazi Germany and Fascist Italy. It would be precisely the latter that would invest a greater economic and logistical effort, due to how Mussolini saw in Spain a possible Mediterranean ally, one akin to his model of Italian fascism. The present investigation attempts to discover how the enemy – in this case the Republican side – was represented in the school textbooks of the last years of the Duce's dictatorship in Italy. The texts were consulted in the Centro di documentazione e ricerca sulla storia del libro scolastico e della letteratura per l’infanza - Museo Paolo e Ornella Ricca of the Università degli Studi di Macerata (Italy). The results show how the school manuals of the time, in subjects such as history, readings, geography or patriotic teachings, reflected an image of the republican side associated with tyranny, demonizing their intervention in the warlike conflict with narratives that exalt violence and anti-Catholicism and identifying them with Soviet communism and anarchy.